Hula ebook - Hakes, Jasmin Iolani (2023)
Named a Best Book of the Summer by Harper's Bazaar and ELLE • Audiofile Magazine Earphones Award Winner • HONOLULU Magazine's Book of the Year About Hawai'i "Stunning . . . An intricately built novel that spans decades, moving in and out of a collective voice, while also telling Hi'i's deeply personal and devastating story of trying to find her way." —Los Angeles Times Set in Hilo, Hawai'i, a sweeping saga of tradition, culture, family, history, and connection that unfolds through the lives of three generations of women—a tale of mothers and daughters, dance and destiny. "There's no running away on an island. Soon enough, you end up where you started." Hi'i is proud to be a Naupaka, a family renowned for its contributions to hula and her hometown of Hilo, Hawaii, but there's a lot she doesn't understand. She's never met her legendary grandmother and her mother has never revealed the identity of her father. Worse, unspoken divides within her tight-knit community have started to grow, creating fractures whose origins are somehow entangled with her own family history. In hula, Hi'i sees a chance to live up to her name and solidify her place within her family legacy. But in order to win the next Miss Aloha Hula competition, she will have to turn her back on everything she had ever been taught, and maybe even lose the very thing she was fighting for. Told in part in the collective voice of a community fighting for its survival, Hula is a spellbinding debut that offers a rare glimpse into a forgotten kingdom that still exists in the heart of its people. "A full-throated chant for Hawai'i . . . It's impossible to come away unchanged." —Kawai Strong Washburn, author of the PEN/Hemingway award-winning Sharks in the Times of Saviors